Ethnobotanical study of medicinal plants used in the treatment of high blood pressure in the region of Tlemcen (Northwestern Algeria) - Sara Hassaïne; Amina Saïdi; Oussama Ali Belhadj (GarVal Editorial Ltda., 2019)
Context: Ethnobotanical study of medicinal plants used in the treatment of high blood pressure in the region of Tlemcen (Northwestern Algeria). Aims: To establish an inventory of medicinal plants recommended by herbalists and used by the local population of Tlemcen against this disease. Methods: The survey was conducted with 242 hypertensive people and 11 herbalists, in 14 municipalities of the Wilaya (Province) of Tlemcen, using a pre-established questionnaire. Results: At the end of this survey, 37 species belonging to 18 families were inventoried. The three most dominant families were Apiaceae (6 species), Lamiaceae and Rosaceae (4 species). The most cited species were Allium sativum L. (48.4%), Citrus limon (L.) Burm (42.7%), Olea europaea var. sativa L. (19.1%), Rosmarinus officinalis L. (9.6%), and Origanum vulgare L. (8.9%). The aerial parts were the most used (23.26%) and most of the remedies were prepared in the form of infusion and decoction (30.5%). Conclusions: The results obtained constitute a highly valuable source of information regarding the traditional treatment of high blood pressure. The selected plants may be the subject of pharmacological studies in order to prove their effectiveness against this disease.